Influence of Teacher-Student Relationships and Special Educational Needs on Student Engagement and Disengagement: A Correlational study - Pérez-Salas, Claudia P.; Parra, Victoria; Sáez-Delgado, Fabiola; Olivares, Himmbler (Frontiers in Psychology, 2021)
Contemporary educational research has found that student engagement and disengagement have a relevant influence on learning outcomes. However, research on the influence of teacher-student relationships in the engagement of students with special education needs (SEN) is scarce. The purpose of this study is to analyze the impact of teacher-student relationships, peer support at school, family support for learning, opportunities to participate at school, and special educational needs on students’ engagement and disengagement using a sample of secondary students with SEN and typical development (TD). Through a non-experimental, correlational, and cross-sectional design, we evaluated 1,020 high school students (340 with SEN, 680 with TD) in the 9th grade (13-19 years old, M = 14.8; SD = .89). Teacher-student relationships, peer support at school, and family support for learning were assessed via subscales from the Student Engagement Inventory (SEI), opportunities to participate at school were measured with a subscale of the School Participation Questionnaire (SP), while engagement and disengagement were measured using the Multidimensional Scale of School Engagement (MSSE). Results show significant statistical differences between SEN and TD students in both student engagement and disengagement indicators. SEN students’ engagement is higher in the cognitive, emotional, and social dimensions than that of TD students. However, they also have higher disengagement in the cognitive and behavioral dimensions. Furthermore, we find SEN students rate their relationships with teachers more highly and perceive more opportunities for school participation than their peers. Further analyses show that teacher-student relationships are positively associated with all dimensions of student engagement and inversely with behavioral and cognitive disengagement. Although correlational, the findings suggest teacher-student relationships and school participation opportunities could be important variables for diminishing disengagement and its negative consequences for both SEN and TD students, while improving student engagement. We discuss these results considering possible implications for educational policies, practices, and research.